2014
DOI: 10.3329/updcj.v3i1.17982
|View full text |Cite
|
Sign up to set email alerts
|

Drug Rehabilitation Center based Survey on Drug Dependence in Dhaka City

Abstract: Abstracts : BackgroundThe study was conducted to know the socio-economic and demographic background of the drug addicts. The study also explored to identify the nature of drug used by the drug addicts and causes of drug addiction. Methods It was a descriptive cross sectional study conducted in a tertiary drug rehabilitation center in Dhaka city, Bangladesh. Purposive sampling strategy was followed and a closed ended questionnaire was utilized for face to face interview with the respondents. The data are analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Excluding alcohol and tobacco, the top ten drugs used across the world were: cannabis, MDMA, amphetamines, cocaine, magic mushrooms, LSD, nitrous oxide, prescribed & non-prescribed opioid medication, ketamine and poppers 6 . The spread of multiple drug use has aggravated the overall problem, personal and social days function, impairment of health, crime and other violent behavior 7 . As a result, it is now growing challenge in Bangladesh, where most of the drug users are being young people, between the ages of 18 and 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…Excluding alcohol and tobacco, the top ten drugs used across the world were: cannabis, MDMA, amphetamines, cocaine, magic mushrooms, LSD, nitrous oxide, prescribed & non-prescribed opioid medication, ketamine and poppers 6 . The spread of multiple drug use has aggravated the overall problem, personal and social days function, impairment of health, crime and other violent behavior 7 . As a result, it is now growing challenge in Bangladesh, where most of the drug users are being young people, between the ages of 18 and 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, there are treatments that can help people to counteract with the disruptive effects of addiction and regain control of lives. Research shows that treatment in rehabilitation centers ensures a better life for the patients who are habitual drug addicts [30]. An addict can achieve a sustained recovery in his or her future life without drugs after getting treatment from rehabilitation centers.…”
Section: Introductionmentioning
confidence: 99%
“…Although evidences are growing in the western context, similar study is almost absent in Bangladesh. A few descriptive studies reported prevalence and sociodemographic nature of SU among University students (14) and recovering patients 15,16) but none of them considered HRQoL of SUs. Such effort in Bangladesh will facilitate intervention by indicating changes in physical, mental and social well-being of various treatment programs.…”
Section: Introductionmentioning
confidence: 99%